THE TRANSFORMATION OF SHARING CULTURE ORGANIZATION CHARACTERISTICS AS A REBOUNDING RESULT OF LOCAL WISDOM VALUE IN IMPROVING INDONESIA'S COMMUNITY COMPETENCE IN THE 21ST CENTURY - Mulyaningsih, Mulyaningsih (JBFEM, 2018)
The IT development in the globalization era influences life to Indonesian society and erodes the fundamental noble value of Indonesian nation in the daily life. Globalization gives effect on Indonesia’s human resources to tend become instant and with uncompetitive, both regional and international, thos needs strong lever through transformation of organizational culture characteristic value. Sharing that has been rebounded with fundamental values and new values from globalization change could be a thinking in the 21st century.This study uses literature study and experiments descriptive towards the local wisdom as collaboration of local culture that is accepted by the internal and external environment. This finding recommends towards the decision making of acting practically in solving problems. Transformation of rebounding value of sharing characteristic as effort of human development attitude values, norms, rules nationally and internationally, human resources to be having fighting spirit, enduring, helping another, is transformed towards building a new level of value in human resources behavior and the profile of Indonesian nation towards the increased competence of human resources in infrastructure, the economic growth of financial upgrade based on kinship and UMKM through value care from various risks that threatens the life of nation and state in the 21st century.